2020
DOI: 10.1016/j.jpainsymman.2020.05.022
|View full text |Cite|
|
Sign up to set email alerts
|

Palliative Care Utilization Among Patients With COVID-19 in an Underserved Population: A Single-Center Retrospective Study

Abstract: Background. As health-care institutions mobilize resources to address the coronavirus disease 2019 (COVID-19) pandemic, palliative care may potentially be underutilized. It is important to assess the use of palliative care in response to the COVID-19 pandemic.Methods. This is a retrospective single-center study of patients with COVID-19 diagnosed via reverse transcriptase-polymerase chain reaction assay admitted between March 1, 2020, and April 24, 2020. An analysis of the utilization of palliative care in acc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 11 publications
2
18
0
2
Order By: Relevance
“…A detailed overview of study characteristics is presented in the Supplementary data, Table S2 . Most studies (84 studies) reported data on COVID-19 patients from China [ 3 , 4 , 10 , 11 , 28–38 , 42–44 , 46–53 , 55 , 56 , 58–77 , 85 , 87 , 88 , 90 , 107–109 , 112 , 118–123 , 132–135 , 137–140 , 142 , 143 , 146–148 , 150–160 ], 27 studies were conducted in the USA [ 11 , 12 , 25 , 27 , 40 , 57 , 78 , 81 , 84 , 94 , 98–101 , 103 , 105 , 111 , 114 , 116 , 124 , 129–131 , 136 , 141 , 145 , 149 , 163 ], 23 studies reported data from Europe [ 26 , 39 , 45 , 54 , 80 , 82 , 83 , 86 , 89 , 91–93 , 95–97 , …”
Section: Resultsmentioning
confidence: 99%
“…A detailed overview of study characteristics is presented in the Supplementary data, Table S2 . Most studies (84 studies) reported data on COVID-19 patients from China [ 3 , 4 , 10 , 11 , 28–38 , 42–44 , 46–53 , 55 , 56 , 58–77 , 85 , 87 , 88 , 90 , 107–109 , 112 , 118–123 , 132–135 , 137–140 , 142 , 143 , 146–148 , 150–160 ], 27 studies were conducted in the USA [ 11 , 12 , 25 , 27 , 40 , 57 , 78 , 81 , 84 , 94 , 98–101 , 103 , 105 , 111 , 114 , 116 , 124 , 129–131 , 136 , 141 , 145 , 149 , 163 ], 23 studies reported data from Europe [ 26 , 39 , 45 , 54 , 80 , 82 , 83 , 86 , 89 , 91–93 , 95–97 , …”
Section: Resultsmentioning
confidence: 99%
“…[3][4][5] Research to date, examining the role of palliative care during this pandemic has focused on strategies developed to implement novel palliative care models in the hospital setting. 6 This research has also highlighted the overall utilisation of palliative care services in patients admitted to the hospital with COVID-19, 7 along with proactive strategies applied in ICU settings to quickly identify patients with palliative care needs. 8 The objective of this study was to examine the utilisation rates of palliative care consultation in critically ill patients with COVID-19 pneumonia admitted to two ICUs in New York City.…”
Section: Introductionmentioning
confidence: 99%
“…10 11 Palliative medicine specialists can make a fundamental contribution precisely because of their ability and experience to work in an organised multiprofessional context and in clinical care environments where difficult choices and limited resources are on the daily teamwork agenda. [10][11][12] An important point to underline is the topic of clinical multidisciplinary work and shared decision making. The innovative element we reckon of interest is the organisation of a work process that allows this integration to be fulfilled on a case-by-case basis with a multidisciplinary approach.…”
Section: Discussionmentioning
confidence: 99%
“…Preparedness of the system to exceptional needs must build both on implementing core palliative care skills in the healthcare system, 14 addressing both the community level 15 16 and the acute care facilities. [10][11][12] It is necessary to think of a hospital where the organisational models are aimed at making possible and dignified any end-of-life path, regardless of the cause that determines it. This will make the difference between a hospital where we do everything possible and a hospital where we believe in a different possible.…”
Section: Short Reportmentioning
confidence: 99%